IMPROVING THE QUALITY OF WORK ON CULVERT UNDERPASS BOX STRUCTURES USING THE LEAN SIX SIGMA METHOD - Rian Darmawan; Budi Susetyo (LPPM Universitas Negeri Jakarta, 2025)
Underpass is an infrastructure built by the government below the ground level to alleviate traffic congestion in large cities. The box culvert system serves as the construction for underpasses. The selection of this system has a significant impact on quality as it will affect the quality of work. The BSD underpass project on the Serpong - Balaraja toll road (Interchance Legok Area STA 9+800) needs to improve its quality because the results of the work do not meet the required standards. The aim of this research is to determine the most influential factors in the quality of underpasses and the implementation of lean six sigma. The research utilizes the Relative Importance Index (RII) method and the Lean Six Sigma method. From the research results, it was found that the most influential factor is ensuring that every incoming material meets the desired quality standards in the quality control variable. In addition, the analysis using Lean Six Sigma in Box Culvert work resulted in a DPMO value of 6058 per one million or equivalent to 4.133 sigma with a yield of 99.39%, thus requiring evaluation through the the DMAIC method Define – Measure – Analyze – Improvement – Control) to reduce defects and improve quality.